1983
DOI: 10.1111/j.1346-8138.1983.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kc‐400 (Polychlorinated Biphenyls) on Porphyrin Metabolism

Abstract: To investigate the influence of polychlorinated biphenyls (PCB) on porphyrin metabolism, Wistar rats were orally administered KC‐400. The mean value of liver/body weight ratio in normal rats was 3.86%, with a range of 3.44% to 5.22%. Their mean blood protoporphyrin level was 23.3 μg/dl packed cell volume (p.c.v.), with a range of 11.8 to 64.4 μg/dl p.c.v., and their mean liver protoporphyrin level was 0.17 μg/gm wet weight, with a range of 0.03 to 0.40 μg/gm wet weight. A feed containing KC‐400 (140–160 ppm) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The analysis of erythrocyte PP was performed using the method described by Honda et al (2) and the methods are shown in Fig. 3.…”
Section: ) Analysis Oferythrocyte Protoporphyrin (Pp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of erythrocyte PP was performed using the method described by Honda et al (2) and the methods are shown in Fig. 3.…”
Section: ) Analysis Oferythrocyte Protoporphyrin (Pp)mentioning
confidence: 99%
“…It is not completely understood what kinds of abnormality in porphyrin metabolism influence ALA-D activity. Previously, we have noticed a difference in protoporphyrin levels among some species when we tried to induce experimental porphyrias (2,3). To elucidate the regulation of ALA-D activity and the differences among species in heme synthetic pathway, we compared ALA-D activity and protoporphyrin (PP) levels in erythrocytes among three different species.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are several reports of abnormal porphyrin metabolism due to PCB; we also observed that PCB induced abnormal porphyrin metabolism in rats (3). In our clinic, we pursued urinary porphyrin analysis in a patient with a history of PCB contamination and heavy alcohol intake (4).…”
Section: Introductionmentioning
confidence: 99%